Pengaruh Stres Kerja dan Beban Kerja Terhadap Komitmen Organisasi pada PT X - Ali, Musyafa; Wolor, Christian Wiradendi; Handaru, Agung Wahyu (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effect of work stress and workload on organizational commitment at PT X. This study used a quantitative approach with 86 employees as respondents. The sampling technique used was saturated sampling, in which the entire population was used as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 29. The results show that work stress has a negative and significant effect on organizational commitment. Workload also has a negative and significant effect on organizational commitment. In addition, work stress and workload simultaneously have a significant effect on organizational commitment. This indicates that the higher the work stress and workload experienced by employees, the lower their organizational commitment.